UWAIS AL-QARNI DALAM PERSPEKTIF PENDIDIKAN ISLAM: MODEL KETELADANAN SPIRITUAL DAN ETIKA SOSIAL BAGI GENERASI MUSLIM - Luthfi (Jurnal Metrum, 2025)
This article explores the exemplary character of Uwais al-Qarni as a spiritual figure relevant to the development of moral character among today’s Muslim youth. Using a descriptive-reflective approach and examining authentic hadiths, classical Islamic literature, and contemporary social contexts, this paper highlights three core traits of Uwais: devotion to his mother, steadfastness in worship despite poverty, and humility despite being praised by the Prophet Muhammad (PBUH). These virtues are analyzed within the framework of a modern crisis of spirituality, hedonism, and the culture of self-image. Uwais is presented as a counter-narrative to viral culture and a symbol of transcendental leadership rooted in sincerity. The study’s implications point toward integrating Uwais’s values into the Islamic religious curriculum and character education programs that emphasize spiritual and social dimensions. The article recommends utilizing Uwais as a character model that fosters not only cognitive achievement but also inner integrity, humility, and social responsibility. Emulating Uwais is expected to inspire a generation that is not only successful in worldly matters but also noble in the sight of heaven.